What is the potential of creativity and drawing for helping and supporting people with special needs? - Tahamit, Naiyirah (2009)
This research is an investigation of ‘what is the potential of creativity and drawing for helping and supporting people with special needs?’ This research raises challenges that many teachers have experienced in working with people with special needs.